Perlindungan Hukum Bagi Anak Sebagai Korban Kekerasan Seksual Di Kabupaten Merauke - Yusril Arba Saputra; Rudini Hasyim Rado (Jurnal Restorative Justice, 2023)
Protection of sexual violence for children is regulated in Law Number. 35 of 2014 on amendments to Law Number. 23 of 2002 concerning Child Protection. The purpose of this research is to find out the form of legal protection for children as victims of sexual violence in Merauke Regency. And to find out the inhibiting factors in the implementation of legal protection for children as victims of sexual violence in Merauke Regency. This study uses an empirical juridical method that uses laws and regulations as a benchmark and looks at facts and phenomena in the field. The results of research on Legal Protection for Children as Victims of Sexual Violence in the Regency are that the police carry out fast handling to be followed up, rehabilitation efforts for children as victims, efforts to protect identity from reporting through the mass media, and providing safety guarantees for child victims in accordance with the Law. Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. The implementation of legal protection for children as victims of sexual violence needs to be supported with adequate facilities and infrastructure. So the authors argue, that it is necessary to have a safe house (shelter) for children who are victims of sexual violence. As well as the need for additional officers in child protection institutions, especially in the Merauke Regency area.